Employment Reallocation and Unemployment Revisited: A Quantile Regression Approach - Theodore Panagiotidis; Gianluigi Pelloni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This study revisits the sectoral shifts hypothesis for the US for the period 1948 to 2011. A quantile regression approach is employed in order to investigate the asymmetric nature of the relationship between sectoral employment and unemployment. Significant asymmetries emerge. Lilien's dispersion index is significant only for relatively high levels of unemployment and becomes insignificant for low levels suggesting that reallocation affects unemployment only when the latter is high. More job reallocation is associated with higher unemployment.
Keywords: C22; C50; E24; 330